2005
DOI: 10.2135/cropsci2004.0663
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adaptation of CIMMYT Bread Wheat to Global High Temperature Environments

Abstract: and lowland Bolivia and Paraguay) and lowland dry areas (e.g., central and peninsular India, Nigeria and A good understanding of the target environment and the extent of Sudan). The most important disease constraints are Helgenotype ϫ environment (G ϫ E) interaction is essential for all cereal breeding programs. Differential adaptation of bread wheat (Triticum minthosporium Leaf Blight (HLB) caused by Bipolaris aestivum L.) to various heat-stressed environments around the world sorokiniana (Sacc.) Shoemaker an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 19 publications
5
65
0
Order By: Relevance
“…For example, analysis of CIMMYT international nursery data shows clear and steady progress in the performance of both bread and durum wheat under drought stress (Ammar et al 2008;Braun et al 2010). In addition, analysis of germplasm released by CIMMYT for hot, irrigated environments shows significant progress, with many of the lines that perform well at the hottest sites also expressing good yield potential under more temperate conditions (Lillemo et al 2005), an important consideration given typical year-to-year variation in temperature. Recent effort has focused on breeding for earlier maturing cultivars that escape terminal heat stress and encompass resistance to diseases associated with warm humid environments (Joshi et al 2011) as well as the highly virulent stem rust strains of the Ug99 lineage.…”
Section: Vulnerability To Climate Changementioning
confidence: 99%
“…For example, analysis of CIMMYT international nursery data shows clear and steady progress in the performance of both bread and durum wheat under drought stress (Ammar et al 2008;Braun et al 2010). In addition, analysis of germplasm released by CIMMYT for hot, irrigated environments shows significant progress, with many of the lines that perform well at the hottest sites also expressing good yield potential under more temperate conditions (Lillemo et al 2005), an important consideration given typical year-to-year variation in temperature. Recent effort has focused on breeding for earlier maturing cultivars that escape terminal heat stress and encompass resistance to diseases associated with warm humid environments (Joshi et al 2011) as well as the highly virulent stem rust strains of the Ug99 lineage.…”
Section: Vulnerability To Climate Changementioning
confidence: 99%
“…Diversity for heat stress tolerance is well established (Al-Khatib and Paulsen, 1990;Reynolds, 1994;Lillemo et al, 2005). Spot blotch tolerance is not well known, and researchers have paid less attention to tolerance than to resistance.…”
mentioning
confidence: 99%
“…More recent and comprehensive analysis (Reynolds et al 1998). Cluster analysis was based on cross-over interaction of genotypes as described by Vargas et al (1998) using CIMMYT international nursery yield data indicated that main genotype clusters correspond to three main types of environment, viz., temperate, continuous heat stress and terminal heat stress, and confirmed relative humidity as an important factor determining G×E within some of these clusters (Lillemo et al 2005).…”
Section: Abiotic-stress Environmentsmentioning
confidence: 62%